2020
DOI: 10.1136/bmjresp-2020-000755
|View full text |Cite
|
Sign up to set email alerts
|

Relative contributions of family history and a polygenic risk score on COPD and related outcomes: COPDGene and ECLIPSE studies

Abstract: IntroductionFamily history is a risk factor for chronic obstructive pulmonary disease (COPD). We previously developed a COPD risk score from genome-wide genetic markers (Polygenic Risk Score, PRS). Whether the PRS and family history provide complementary or redundant information for predicting COPD and related outcomes is unknown.MethodsWe assessed the predictive capacity of family history and PRS on COPD and COPD-related outcomes in non-Hispanic white (NHW) and African American (AA) subjects from COPDGene and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…In addition, PRS were still significant after adjusting for family history. All of these indicated that while family history includes at least some genetic components of AUD, PRS provided complementary information, and together they improve the ability to evaluate disease risk as having been demonstrated in previous studies (Abraham et al, 2019;Gronberg et al, 2015;Hujoel et al, 2021;Kachuri et al, 2020;Lu et al, 2018;Moll et al, 2020). As noted previously, early alcohol intervention programs with high-risk individuals were effective in reducing the incidence of AUD (Bersamin et al, 2007;Cronce & Larimer, 2011;Kaner et al, 2007Kaner et al, , 2018Knox et al, 2019;Solberg et al, 2008;Welter et al, 2020;Whitlock et al, 2004); PRS and family history can lead to expedited risk identification, which in turn can guide best practices around these programs, making targeted and personalized prevention strategies possible.…”
Section: Discussionmentioning
confidence: 55%
“…In addition, PRS were still significant after adjusting for family history. All of these indicated that while family history includes at least some genetic components of AUD, PRS provided complementary information, and together they improve the ability to evaluate disease risk as having been demonstrated in previous studies (Abraham et al, 2019;Gronberg et al, 2015;Hujoel et al, 2021;Kachuri et al, 2020;Lu et al, 2018;Moll et al, 2020). As noted previously, early alcohol intervention programs with high-risk individuals were effective in reducing the incidence of AUD (Bersamin et al, 2007;Cronce & Larimer, 2011;Kaner et al, 2007Kaner et al, , 2018Knox et al, 2019;Solberg et al, 2008;Welter et al, 2020;Whitlock et al, 2004); PRS and family history can lead to expedited risk identification, which in turn can guide best practices around these programs, making targeted and personalized prevention strategies possible.…”
Section: Discussionmentioning
confidence: 55%
“…The systematic search resulted in 11 publications; subsequently, two additional studies were included, following perusal of references. Moll et al 20 used data from the COPDGene study and then replicated the study by using data from the ECLIPSE cohort. Results from the two analyses are displayed as two separate studies in the Results section ( Tables 1–3 ).…”
Section: Resultsmentioning
confidence: 99%
“… Adoptees born between 1932 and 2004 To examine the risk of COPD in adoptees with parental COPD in either biological or adoptive parents or in both biological and adoptive parents. Cases: Adoptees with an ICD 7–10 code of COPD in national registries Controls: Adoptees without COPD No information on smoking history COPD based on ICD 7–10 codes from national registries No information on smoking history Moll 20 2020 Case–control, Multicentre, Prognostic study 12 countries ECLIPSE study To assess the predictive performance of a polygenetic risk score and family history. (A replication cohort of the COPDGene cohort.)…”
Section: Resultsmentioning
confidence: 99%
“…Lassosum sets its unique PRS structure through applying L1 penalized regression framework on GWA summary statistics and a LD reference panel [19,20]. Similar to LDpred, we also chose the UK Biobank training set as the LD reference panel in the Lassosum setting.…”
Section: Prs Benchmark Methodsmentioning
confidence: 99%